1998
DOI: 10.1295/polymj.30.388
|View full text |Cite
|
Sign up to set email alerts
|

Order-Disorder Transition of Symmetric Poly(styrene-b-2-vinylpyridine) in Bulk and Solution

Abstract: ABSTRACT:Order-disorder transitions (ODT) of symmetric poly(styrene-b-2-vinylpyridine) in a common good solvent and bulk were determined by dynamic rheological and small-angle neutron scattering measurements. ODT conditions determined by both methods are consistent with each other and the degree of polymerization dependence of critical volume fraction in solution at almost constant temperature agrees with the theoretical prediction for semidilute solutions. However, semidilute behavior persists to a much highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…Figure 1 also displays the concentration scaling of the styrene-isoprene interaction parameter, , at the OOT and ODT, as determined previously, 9 using the following expression (based on the styrene segment volume) determined from extensive results on lamellar-forming SI solutions and melts: 7 The solid line through the G 1 f C 1 OOTs follows the dilution approximation, i.e., OOT ∼ φ -1 , whereas the ODTs display the stronger dependence of ODT ∼ φ -1.4 , similar to the scaling of φ -1.6 found previously for lamellar diblocks in neutral good solvents. 7,8 For comparison, the predicted dilution approximation 7 scaling of the ODT is shown as the dashed line extending down from the melt T ODT . It overestimates T ODT by as much as 60°C at φ ) 0.55.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 also displays the concentration scaling of the styrene-isoprene interaction parameter, , at the OOT and ODT, as determined previously, 9 using the following expression (based on the styrene segment volume) determined from extensive results on lamellar-forming SI solutions and melts: 7 The solid line through the G 1 f C 1 OOTs follows the dilution approximation, i.e., OOT ∼ φ -1 , whereas the ODTs display the stronger dependence of ODT ∼ φ -1.4 , similar to the scaling of φ -1.6 found previously for lamellar diblocks in neutral good solvents. 7,8 For comparison, the predicted dilution approximation 7 scaling of the ODT is shown as the dashed line extending down from the melt T ODT . It overestimates T ODT by as much as 60°C at φ ) 0.55.…”
Section: Resultsmentioning
confidence: 99%
“…29) Since T ODT for other M w samples cannot be determined by DMA, we determined temperature, T, dependence of χ parameter by SANS measurement using the same deutrated sample DP17 (M n : 1.2×10 4 , M w /M n : 1.05) in a much wider T range than in the previous work. 29) Using the T dependence of χ, ODT of other samples are estimated. Then the states of a few samples are confirmed by small angle X-ray scattering (SAXS) measurements at selected T s.…”
Section: ˚C By Dynamic Mechanical Analysis (Dma) In a Previousmentioning
confidence: 99%
“…In a previous paper 29) , we reported that shear rate, To compare viscoelastic properties of diblock copolymers and component homopolymers, the behaviors of symmetric poly(styrene-block-2-vinylpyridine)s (SP)s, having almost the same components' viscoelastic properties 32) as well as other physical properties [33][34][35] , are studied under the dynamic and steady shear flow in a common good solvent near the ODT. [29][30][31] Corresponding structural changes under the flow are examined by small angle neutron scattering (SANS) using deutrated SP (DP).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations